The Emplementation of Health Protocol Facilities through Handwashing and Social Distancing Education in The Tourism Area of Pecel Kampong, Ngerangan Village Klaten Regency - Novia Sari Ristianti; Nurhadi Bashit; Desyta Ulfiana; Grandy Loranessa Wungo; Fauzi Janu Amarrohman; Hardi Wibowo (ABDIMAS: Jurnal Pengabdian Masyarakat, 2021)
The COVID-19 pandemic has plagued the entire world, including Indonesia. The step to breaking the spread chain of COVID-19 is to apply health protocols such as handwashing and social distancing. The Covid-19 case in Klaten Regency Central Java for ten weeks until early February 2021 with the status of the Red Zone and death rate is 14.1 percent. Ngerangan Tourism Village has a thematic kampong with culinary and nature attractions, such as Pecel Kampong. The number of visitors reaches 600 tourists per day. This causes tourist sites to be clusters most prone to the spread of COVID-19 and must be equipped with adequate health protocols. Therefore, this service aims to implement health protocols during the Covid 19 pandemic through hand washing and social distancing. The service method has three stages, namely information, guidance, and habitual independence. The output of this service is in the form of technology that is socialized and donated in handwashing behavior in the form of 3 portable footstep sinks, four jerry cans of handwashing soap, one hand washing educational banner, and one banner for implementing health protocols. Meanwhile, the technology that was socialized and granted in the implementation of Social Distancing was in the form of 1 banner for implementing social distancing and 20 stickers indicating the implementation of social distancing.